Post-acute sequelae of covid-19 six to 12 months after infection: population based study. (13th October 2022) - Peter, Raphael S; Nieters, Alexandra; Kräusslich, Hans-Georg; Brockmann, Stefan O; Göpel, Siri; Kindle, Gerhard; Merle, Uta; Steinacker, Jürgen M; Rothenbacher, Dietrich; Kern, Winfried V
Abstract: Objectives: To describe symptoms and symptom clusters of post-covid syndrome six to 12 months after acute infection, describe risk factors, and examine the association of symptom clusters with general health and working capacity. Design: Population based, cross sectional study Setting: Adults aged 18-65 years with confirmed SARS-CoV-2 infection between October 2020 and March 2021 notified to health authorities in four geographically defined regions in southern Germany. Participants: 50 457 patients were invited to participate in the study, of whom 12 053 (24%) responded and 11 710 (58.8% (n=6881) female; mean age 44.1 years; 3.6% (412/11 602) previously admitted with covid-19; mean follow-up time 8.5 months) could be included in the analyses. Main outcome measures: Symptom frequencies (six to 12 months after versus before acute infection), symptom severity and clustering, risk factors, and associations with general health recovery and working capacity. Results: The symptom clusters fatigue (37.2% (4213/11 312), 95% confidence interval 36.4% to 38.1%) and neurocognitive impairment (31.3% (3561/11 361), 30.5% to 32.2%) contributed most to reduced health recovery and working capacity, but chest symptoms, anxiety/depression, headache/dizziness, and pain syndromes were also prevalent and relevant for working capacity, with some differences according to sex and age. Considering new symptoms with at least moderate impairment of daily life and ≤80% recovered general health or working capacity, the overall estimate for post-covid syndrome was 28.5% (3289/11 536, 27.7% to 29.3%) among participants or at least 6.5% (3289/50 457) in the infected adult population (assuming that all non-responders had completely recovered). The true value is likely to be between these estimates. Conclusions: Despite the limitation of a low response rate and possible selection and recall biases, this study suggests a considerable burden of self-reported post-acute symptom clusters and possible sequelae, notably fatigue and neurocognitive impairment, six to 12 months after acute SARS-CoV-2 infection, even among young and middle aged adults after mild infection, with a substantial impact on general health and working capacity. Trial registration: German registry of clinical studies DRKS 00027012.